Morfologinių formų kaita J. Jaknavičiaus Evangelijų leidimuose - Lučinskienė, Milda (Baltistica, 1998)
CHANGES OF MORPHOLOGICAL FORMS IN DIFFERENT EDITIONS OF J. JAKNAVIČIUS GOSPELS The endings -mus and -ms of dative plural are characteristic of the Eastern variant of Gospels (year 1647) of Jonas Jaknavičius. From 1705 Gospels were reworked with their language adapted to the central variant of the written language. In the year 1705, these endings -mus and -ms were substituted by the ending -mis of dat. pl. In the majority of cases the allative was corrected, as compared to illative and adessive which were corrected in rare cases. These correction trends are reflected in Table 1 and 2.